Sex ratio of the Eurasian Wigeon Anas penelope during spring migration at Angarnsjöängen, Uppland, 1995—2005 - Söderholm, Svante (Ornis Svecica, 2007)
The sex ratio of the Eurasian Wigeon Anas penelope and its seasonal variation was studied during eleven spring migrations at Angarnsjöängen, Sweden (59° 33'N, 18° 10'E). The main passage of birds occurred in the second half of April, and the migration had almost ceased after 15 May. Eurasian Wigeons recorded after this date were mainly males and probably mostly non-breeders, moult migrants or stragglers. The fraction of males was 0.53 (SD=0.028), and there was no difference between years. Neither was there a correlation between the fraction of males and the flock size. About 95% of the females and 85% of the males were paired during the stopover.